OP63 Body Size and Body Composition: A Comparison between Children in India and in the UK through Infancy and Early Childhood. (10th September 2013) - D'Angelo, S; Crozier, S R; Chittaranjan, Y; Joglekar, C; Lubree, H; Fall, C H; Inskip, H M
Abstract : Background: Indian children have been shown to be smaller in all body measurements compared with white Caucasian British children at birth, one and four years, but they show a particular pattern of smallness, with relative sparing of subcutaneous fat– the so-called 'thin-fat' phenotype. Recently, Indian children at age 6 years were found to have a higher body fat percentage from DXA measurements than white British children, despite a lower BMI. However, no study has compared Indian anthropometric measurements at birth and at multiple ages through early childhood to 6 years with a large (> 500) population sample of British children, using the same measurement protocols throughout. Methods: We used data from 631 liveborn, singleton children from the Pune Maternal Nutrition Study (PMNS) and 3012 liveborn, singleton, white British children from the Southampton Women's Survey (SWS), which included anthropometric measurements at birth and 1, 2, 3 and 6 years. t-tests and Mann-Whitney U-tests were used to compare the means and medians of the two populations. Birth measurements were adjusted for gestational age and sex, using linear regression, while the measurements at the other ages were adjusted only for sex. Southampton measurements were used as a reference and standard deviation (SD) scores were generated: Pune SD score = (Pune observation-Southampton mean)/ (Southampton SD). Results: At all ages and for all anthropometric measurements considered, Pune children were smaller than those in Southampton. At all ages after birth, the largest difference was found in head circumference, followed by mid-upper arm circumference and weight. At birth and through infancy and childhood, subscapular skinfold thickness was always the most spared measurement, indicating that the body composition of Pune children was characterised by fat preservation at all ages. Conclusion: This study suggests that the previously described 'thin-fat phenotype' characterises Indian babies not only at birth but also through infancy and childhood up to 6 years of age. Compared with the Southampton children, they are smaller but have greater preservation of subcutaneous fat, and this pattern is sustained to age 6 years. It is well known that adult Indians have a higher percentage body fat than those from European populations, but this propensity is established before birth and does not alter through early life.